Identification of Andesite Rocks Using Dipole-Dipole Geoelectric Method in Batursari Subdistrict, Pekalongan Regency, Central Java - Firdos Bahar Sidik; Rama Wahyu Nurawi; Haris Muhlisin; Wrego Seno Giamboro; Wahyu Hidayat (East Asian Journal of Multidisciplinary Research, 2023)
A study has been conducted to identify andesite rocks using the dipole-dipole geoelectric resistivity method in the Batursari Subdistrict, Pekalongan Regency, Central Java Province. Measurements were taken along 12 Lines stretching from northwest to southeast, with a Line length of 280 m and electrode spacing of 10 m. The aim of this research was to model the 2D resistivity value Line of the path, determine the type of andesite rock, and assess the depth of the rock in the study area. Based on data processing results, four lithology units were identified: resistivity values ranging from 0 to 150 Ωm were interpreted as soil, 150 to 250 Ωm as weathered andesite, 250 to 400 Ωm as moderate andesite, and resistivity values from 400 Ωm to 3000 Ωm were interpreted as fresh andesite.